Cross‐Polarization Electron‐Nuclear Double Resonance Spectroscopy. Issue 18 (13th November 2015) - Rizzato, Roberto; Bennati, Marina
Abstract: Magnetic nuclei in the proximity of a paramagnetic center can be polarized through electron‐nuclear cross‐polarization and detected in electron‐nuclear double resonance (ENDOR) spectroscopy. This principle is demonstrated in a single‐crystal model sample as well as on a protein, the β2 subunit of E.coli ribonucleotide reductase (RNR), which contains an essential tyrosyl radical. ENDOR is a fundamental technique to detect magnetic nuclei coupled to paramagnetic centers. It is widely employed in biological and materials sciences. Despite its utility, its sensitivity in real samples is about one to two orders of magnitude lower than conventional electron paramagnetic resonance, thus restricting its application potential. Herein, we report the performance of a recently introduced concept to polarize nuclear spins and detect their ENDOR spectrum, which is based on electron‐nuclear cross polarization (eNCP). A single‐crystal study permits us to disentangle eNCP conditions and CP‐ENDOR intensities, providing the experimental foundation in agreement with the theoretical prediction. The CP‐ENDOR performance on a real protein sample is best demonstrated with the spectra of the essential tyrosyl radical in the β2 subunit of E.coli RNR. Abstract : The be all and ENDOR : The cross‐polarization electron‐nuclear double resonance (CP‐ENDOR) experiment provides an attractive new method to record ENDOR spectra. This is carried out on a single‐crystal model sample as well as a real protein sample with improved performance with respect to the standard Davies sequence.